Pregnancy in the rudimentary horn - the culprit behind a catastrophical outcome - Mayuri Ahuja; Ruchi Srivastava; Shehla Jamal (New Indian Journal of OBGYN, 2019)
Pregnancy in a non-communicating rudimentary horn is of very rare occurrence. Delayed and initial misdiagnosis can result in catastrophic outcome both for the fetus as well as the mother. We present a case of 24 years old G3P2L1 with ruptured pregnancy in a rudimentary horn which due to misdiagnosis resulted in maternal near miss.